Comparison of in-house HIV-1 genotypic drug resistant test with commercial HIV-1 genotypic test kit - Praparattanapan,J. (IOS Press, 2015)
Background: The use of combination antiretroviral therapy (cART) has become a standard of care in the treatment of HIV infection. However, antiretroviral drug resistance occurs in a substantial number of patients. In resource-limited settings, genotypic resistance assay using a commercial kit is costly. Objective: Focus on the validation of an in-house HIV-1 specific genotypic drug resistance assay in Thai patients failing cART. Materials and methods: Results of HIV-1 genotypic drug resistance assay was evaluated by comparing an inhouse method to a commercial test. The TRUGENE HIV-1 genotyping kit was used in 79 plasma specimens (49 from HIV patients failing cART therapy and 30 from proficiency testing panels). Results: The results from the in-house assay were comparable to those obtained from the TRUGENE HIV-1 genotyping kit with >99.0% codon-to-codon agreement. The lower limit of detection by the in-house assay was approximately 100 copies/mL of HIV-1 RNA. In addition, this in-house assay would allow testing of samples from patients infected with HIV-1 subtype other than B. Conclusion: The in-house HIV-1 genotypic drug resistance assay may be used as an alternative to commercial kits, particularly in resource limited settings.